Meningkatkan Ketahanan Finansial: Peran Literasi Keuangan Digital dalam Mengatasi Risiko Pinjaman Online dan Paylater di Kota Banjarmasin - Sondakh, Antonius Grivaldi; Hayat, Atma; Sarwani, Sarwani; Safrida, Lili; Hardi, Enny; Amalia, Wia Rizqi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The use of digital financial technologies, such as online lending platforms and paylater payment schemes, has significantly increased among the public, including residents of Banjarmasin City, particularly among younger generations such as Millennials and Generation Z. Although these services provide convenient access to financial resources, insufficient digital financial literacy has heightened financial risks, including debt entrapment associated with paylater services and online loans. This community engagement initiative aimed to enhance financial resilience through digital financial literacy education, with a focus on understanding potential risks and promoting prudent use of digital financial services. The program was implemented through a seminar primarily targeting young people in Banjarmasin City. The materials covered fundamental concepts of financial literacy, identification of illegal online lending platforms, budgeting simulations, and strategies to prevent dependency on paylater services. The results indicate an improvement in participants’ understanding of the risks associated with digital financial services and their ability to plan personal finances effectively. Furthermore, participants demonstrated a more critical attitude toward online loan offers and the use of paylater schemes. This initiative confirms that digital financial literacy represents a strategic approach to strengthening the financial resilience of young generations in Banjarmasin City.